1977
DOI: 10.1139/o77-049
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting inosinate synthesis and inosine triphosphate accumulation in human erythrocytes

Abstract: Measurements of rates of inosinate synthesis from radioactive hypoxanthine by human erythrocytes show a large degree of individual variation. Rates of inosinate synthesis also vary with the pH and phosphate concentration of the incubation medium. This may be due to changes in the rate of phosphoribosyl pyrophosphate synthesis, and the stimulatory effect of phosphate on this process seems to be more important than the inhibitory effect of 2,3-diphodphoglycerate. The rate of inosinate synthesis, and especially t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…They also suggested that the following two phosphorylation steps are performed by nucleoside monophosphate kinase and NDP kinase with ATP serving as the phosphate donor. Next researchers found that ITP could be synthesized from hypoxanthine [3133] favoring the second theory for the generation of IMP. All of these studies focused on erythrocytes.…”
Section: Origins Of Non-canonical Nucleotidesmentioning
confidence: 99%
See 1 more Smart Citation
“…They also suggested that the following two phosphorylation steps are performed by nucleoside monophosphate kinase and NDP kinase with ATP serving as the phosphate donor. Next researchers found that ITP could be synthesized from hypoxanthine [3133] favoring the second theory for the generation of IMP. All of these studies focused on erythrocytes.…”
Section: Origins Of Non-canonical Nucleotidesmentioning
confidence: 99%
“…3, which could then be phosphorylated to ADP and ATP, which in turn could be deaminated to IDP and ITP. However, erythrocytes lack adenylosuccinate synthetase and thus cannot form AMP from IMP [33]. Nonetheless, this pathway to ITP is a possibility for the other cell types examined.…”
Section: Origins Of Non-canonical Nucleotidesmentioning
confidence: 99%